(untitled) (Research Data Journal for the Humanities and Social Sciences, 2024)
The authors present a dataset containing transcriptions of manuscripts of the Middle Dutch strophic poem Martijn Trilogy by the Flemish poet Jacob van Maerlant. Of his very large oeuvre, Maerlant’s Strophic Poems had the longest tradition: originally written in the thirteenth century, copyists and printers continued to disseminate them until about 1500. These ten shorter poems on social, religious, and ethical issues stand out for their unusual and complex stanza form. The Martijn Trilogy was his most successful strophic poem: 17 text witnesses are extant, and the trilogy was imitated and even translated into French and Latin. This dataset contains hyperdiplomatic transcriptions of all witnesses, amounting to a total of 15,814 verses or 79,337 tokens. This open-access dataset abides by the fair principles, is licensed under a cc-by-sa license, and is made available in multiple, complementary file formats. Since these transcriptions are strictly diplomatic, this corpus offers valuable possibilities for research data journal for the humanities and social sciences 9 (2024) research on scribal attributions (scribal profiling), abbreviations, stemmatology, textual stability and more.